2005
DOI: 10.1038/sj.ijo.0803069
|View full text |Cite
|
Sign up to set email alerts
|

‘Adventure therapy’ combined with cognitive-behavioral treatment for overweight adolescents

Abstract: Objective: Since peers have such an important influence on adolescents, we evaluated the efficacy of adding peer-based 'adventure therapy' to a standard cognitive-behavioral weight control program for overweight adolescents. Methods: Adolescents (N ¼ 76) aged 13-16 years and 20 to 80% overweight (M ¼ 60.56%, s.d. ¼ 15.17%), were randomly assigned to one of two treatment conditions: cognitive-behavioral group treatment with 'adventure therapy' similar to Outward Bound s (cognitive-behavioral treatment with peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
2
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(128 citation statements)
references
References 34 publications
6
114
2
6
Order By: Relevance
“…Besides behavioral therapy of eating and physical activity behaviors, dietary, and physical exercise courses, which have been regarded as significant components of weight-loss interventions, 5,6 treatment of obesity in childhood should involve the family environment. [7][8][9] Even though intervention programs have proven effective in reducing weight and have also shown reasonable long-term success, [10][11][12][13][14] far from all attendees respond to therapy. Percentages of those who do not finish interventions mostly average 20% 10,11,13,15 and of those who complete about 37% fail to reduce overweight more than 5%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides behavioral therapy of eating and physical activity behaviors, dietary, and physical exercise courses, which have been regarded as significant components of weight-loss interventions, 5,6 treatment of obesity in childhood should involve the family environment. [7][8][9] Even though intervention programs have proven effective in reducing weight and have also shown reasonable long-term success, [10][11][12][13][14] far from all attendees respond to therapy. Percentages of those who do not finish interventions mostly average 20% 10,11,13,15 and of those who complete about 37% fail to reduce overweight more than 5%.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Even though intervention programs have proven effective in reducing weight and have also shown reasonable long-term success, [10][11][12][13][14] far from all attendees respond to therapy. Percentages of those who do not finish interventions mostly average 20% 10,11,13,15 and of those who complete about 37% fail to reduce overweight more than 5%. 13,14 Particularly in childhood, such negative experiences should be avoided because motivation to control overweight decreases with each failure.…”
Section: Introductionmentioning
confidence: 99%
“…Nos résultats rejoignent de plusieurs façons ceux d'autres études (Gass, et al, 2003;Haluza Delay, 1999;Harris, et al, 2005;Jelalian, Mehlenbeck, Richardson Lloyd, Birmaher, & Wing, 2006;Stevens, et al, 2004 Au plan méthodologique, certains auteurs suggèrent davantage de rigueur au plan méthodologique. En effet, les études du domaine de l'aventure sont difficilement comparables entre elles, puisque les programmes diffèrent en plusieurs points : ils ne sont pas tous de la même durée, ni de la même structure, tiennent des objectifs différents, etc.…”
Section: Les Forces Individuellesunclassified
“…Additional details of the intervention components have been described elsewhere. 10,13 Measures All measures were obtained at baseline, at the end of the 16-week intervention, and at 12 and 24 months following randomization. Participants were offered monetary compensation for time spent completing initial and follow-up evaluations.…”
Section: Interventionmentioning
confidence: 99%
“…Very few lifestyle interventions have exclusively targeted adolescents, and few of these provide long-term effectiveness results, rarely going beyond 6-or 12-month outcomes. Of note, a recent trial by Savoye and colleagues 6 found that obese children and teenagers (ages [8][9][10][11][12][13][14][15] who were randomized to a 12-month lifestyle intervention were more likely to maintain weight loss at 24-month follow-up than those randomized to a clinic control group; however, this sample was not comprised exclusively of adolescents and was limited by a poor retention rate (43.7%) at 24-month follow-up. A 2-year, family-based behavioral treatment program for overweight adolescents (mean age = 13 years) in China found a BMI reduction of 9.8% among those receiving monthly home visits, as opposed to no cumulative weight change among the control group.…”
mentioning
confidence: 99%